Optimasi Sistem Irigasi Lahan Tada Hujan menggunakan Algoritma Ant Colony Optimization berbasis Tenaga Surya - Abdul Haris (Sekolah Tinggi Teknik - PLN, 2021)
Indonesia is a country that has vast agriculture and has a majority source of income as farmer. The agriculture area still cannot be optimized considering that still a lot of dry agriculture land and have not got good irrigation system, several problems that cause are still a lot of dry agriculture which higher position of irrigation system available and there are limited land so that if irrigation system built or DAM then operational coast outweigh of impact on the land, another problem occurs is limited ability of community for built independent and modern irrigation system so that assistance is needed and technology that can be utilized as resource for built independent and modern irrigation system. One of potential resource in Indonesia is energy of sun which can be converted to electric power, this is energy very much in Indonesia, so that can be using as energy to pump water from springs to be distributed to dry agriculture land. To be able to reduce human power and monitoring this paper using Ant Colony Optimization as computation system. This algorithm used to optimized water distribution evenly on dry agriculture land which is adapted to the soil conditions.